Ciplukan (Physalis Angulata Linn.) Extract Compounds Potential on High-Fat Diet Induced Nonalcoholic Fatty Liver Disease (NAFLD) for Liver Anti-Fibrotic Drug Development - Enny Rohmawaty; Sumartini Dewi; Aziiz Mardanarian Rosdianto; Hermin Aminah Usman; Ade Zuhrotun; Rini Hendriani; Yoga Windhu Wardhana; Savira Ekawardhani; Hesti Lina Wiraswati; Andri Reza Rahmadi; Nenny Agustanti; M. Begawan Bestari (Indonesian Journal of Pharmacy, 2023)
An increasing percentage of people have or are at risk to develop the non-alcoholic fatty liver disease (NAFLD) worldwide. Fibrosis has also been identified as the most important predictor of prognosis in patients with NAFLD. Ciplukan (Physalis angulata Linn.)  was reported to have antifibrotic potency in CCl4-induced liver fibrotic rats. This study was conducted to evaluate the antifibrotic effect of ciplukan extract through repairing the liver function, anti-inflammatory, and lowering cholesterol. The liver fibrosis model using 20% margarine was injected subcutaneously 8 times with a frequency of twice a week for 4 weeks in 35 male and 35 female Wistar strains which were divided into 7 groups.  Furthermore, the rats were given Ciplukan extract (CPL) orally starting the 6th week of treatment with 2 different doses, namely 13.5 mg (CPL-1) and 27 mg (CPL-2) every day for 4 weeks. The histopathological changes of liver fibrosis was analyzed using Haematoxylin Eosin (HE) staining. Determination of serum IL-6 and TGF-β1 levels was carried out by the ELISA method. ALT and cholesterol levels were tested using a diagnostic kit. Single and multiple doses of ciplukan extract with or without standard therapy (Vitamin E) can reduce fibrotic scores up to 1.30±0.95 (p=0.001), TGF-β1 levels up to 24.20±2.02 ng/mL (p = 0.000), IL-6 levels up to 1.68±0.52 pg/mL (p=0.156), ALT levels up to 104.57±2.02 U/mL (p=0.001), and cholesterol levels up to 81, 07±2.02 mg/dL (p=0.000). Ciplukan herb ethanol extract was proven to have liver antifibrotic activity, which means it has potential as a liver fibrotic drug. The liver antifibrotic effect of Ciplukan herb was shown by a histopathological decrease in liver fibrosis scores accompanied by a decrease in TGF-β1, IL-6, ALT, and cholesterol levels.Keywords: Physalis angulata Linn (Ciplukan), liver fibrosis, NAFLD, ALT, Cholesterol, IL-6